Falta injustificada del personal de enfermería a su jornada laboral: un enfoque explicativo. - García-Puga, Julio Alfredo (Universidad de Sonora, 2019)
This essay is a reflection on the phenomenon of unjustified absence of nurses to their workday at a public hospital in Sonora, Mexico, which is a second level hospital dependent of the Health Secretary. Although the phenomenon has been studied from different approaches and has raised the multidimensional nature of the problem, in this essay is approached from the perspective of social capital of nurses and the logic of social practices, for it is used as a theoretical approach to the notion social capital and Pierre Bourdieu practical reason, all articulated with the structural working conditions of the hospital institution. Based on the exposed by Ives Morieux is done the proposal to articulate six institutional rules in nursing practice as a coadjuvant to prevent unexcused absence of nurses. Such as preliminary conclusions considers that nurses are products of their living conditions and employment status therefore instead of blaming individuals the structure could be responsible for labor unexcused absence.